Training and Assistance in Making E-LKPD Using “LiveWorksheets” Aplication at SD Alam Cordova Probolinggo - Ani Anjarwati; Ryzca Siti Qomariyah; Alvin Kurnia; Putri Fatimattus Az Zahra; Muhimma Yatun Nisa’ul Ulya (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
In the era of the industrial revolution 4.0, we are in an era of increasingly developing technology so that it requires people to be technologically literate, especially to the world of education. The industrial revolution 4.0 provides support for the learning process. The industrial era 4.0 is very helpful for educational problems that occur during the COVID-19 pandemic. During the COVID-19 pandemic, the learning process was carried out using branded learning by combining face-to-face and online learning. So that educators find it difficult to choose learning methods and media after carrying out full school online. However, educators are required to continue to provide learning materials and assignments to students because of the demands to obtain student grades on each thematic. This activity aims to introduce the LKS application directly to assist educators in making E-LKPD which can be a means of transferring students' knowledge to understand the material and get grades automatically. The training method is carried out online with the Google Meet application. The material is divided into four points and delivered in two stages, followed by the teachers of SD Alam Cordova. The results of this online “Liveworksheets” training show that teachers can apply “Liveworksheets” well.